2013
DOI: 10.1590/s0102-05362013000300006
|View full text |Cite
|
Sign up to set email alerts
|

Fruit yield of strawberry stock plants after runner tip production by different cultivars

Abstract: The main objective of this research was to determine fruit yield of strawberry (Fragaria x ananassa) stock plants in a cropping system after producing runner tips and plug plants. Micropropagated stock plants were planted in a soilless growing system. Runner tips bearing at least one visible root nodule were harvested at 43, 66 and 87 days after planting, rooted and planted as multiplied stock plants for producing plug plants. same cultivars were planted as control for fruit production. Early fruit yield and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(1 reference statement)
0
3
0
1
Order By: Relevance
“…In the soilless production of tips for plug transplants, the growth of mother plant is not a matter of interest because mother plants should be discarded at the end of the tip production period. This would be an advantage only in the case that such plants were to be used for further production of fruit, as suggested by Dal Picio et al (2013). Nevertheless, these authors showed that, although high fruit yield can be reached by mother plants after tip production, fruit size is reduced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the soilless production of tips for plug transplants, the growth of mother plant is not a matter of interest because mother plants should be discarded at the end of the tip production period. This would be an advantage only in the case that such plants were to be used for further production of fruit, as suggested by Dal Picio et al (2013). Nevertheless, these authors showed that, although high fruit yield can be reached by mother plants after tip production, fruit size is reduced.…”
Section: Resultsmentioning
confidence: 99%
“…In spite the existence of these studies on strawberry wild species, no similar records were found for the cultivated species Fragaria x ananassa. A vigorous growth of mother plants was reported during the propagation phase of this species for producing runner tips (Dal Picio et al, 2013), which represents a waste of carbon assimilates, water and mineral nutrients. Therefore, it can be hypothesised that defoliation can be used to reduce growth of mother plants, without reducing emission and growth of runner tips for plug transplant production.…”
Section: Introductionmentioning
confidence: 99%
“…However, most strawberry plants used in the country have been imported from Patagonia (Argentina and Chile), due to excellent local growing conditions (Antunes and Peres, 2013;Gonçalves et al, 2016), which enable high resource (carbohydrate) accumulation (Cocco et al, 2016). This situation has made producers get increasingly dependent on plant importation and has obliged them to adapt cultivation to the period of plant arrival, which is often not the recommended one for growing strawberries in Brazil (Dal Picio et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…No Brasil, são produzidas, aproximadamente, 150.000 toneladas da fruta, em uma área de 4.200 hectares (FAGHERAZZI et al 2017), e a produção é baseada em lavouras estabelecidas a partir de mudas de raízes nuas. As mesmas são produzidas a partir de pontas de estolão que são emitidas pela planta matriz e enraizadas diretamente no solo, sendo este o principal sistema de produção de mudas utilizado no país (DAL PICIO et al 2013).…”
unclassified